Retinal imaging including optical coherence tomography angiography for detecting active choroidal neovascularization in pseudoxanthoma elasticum. (14th November 2018) - Birtel, Johannes; Lindner, Moritz; Mishra, Divyansh K.; Müller, Philipp L.; Hendig, Doris; Herrmann, Philipp; Holz, Frank G.; Fleckenstein, Monika; Gliem, Martin; Charbel Issa, Peter
Abstract : Importance: The diagnostic accuracy of different retinal imaging modalities to detect active choroidal neovascularization (CNV) in pseudoxanthoma elasticum (PXE) is essential to enable a correct diagnosis but is currently poorly understood. Background: Optical coherence tomography (OCT), fluorescein angiography (FA) and OCT angiography (OCT‐A) are employed in daily practice, but a systematic comparison of these imaging techniques is lacking. Design: Retrospective, observational study. Participants: Twenty patients (31 eyes) with PXE. Methods: OCT, FA and OCT‐A imaging was performed in each eye and graded separately by independent readers. Main Outcome Measures: Diagnostic accuracy, sensitivity and specificity to detect CNV‐activity of each modality and longitudinal change of CNV size measured by OCT‐A. Results: OCT showed the highest diagnostic accuracy (kappa = 0.57) in comparison to OCT‐A or FA (kappa = 0.39 and 0.37, respectively). OCT‐A, OCT and FA showed a diagnostic sensitivity of 0.9, 0.85 and 0.6, and a diagnostic specificity of 0.45, 0.72 and 0.82, respectively. Evaluation of longitudinal OCT recordings (24 eyes) resulted in optimal sensitivity and specificity (kappa = 1.0). Although median CNV size assessed using OCT‐A remained stable on longitudinal measures of seven eyes, two eyes showed a distinct increase over time despite anti‐vascular endothelial growth factor treatment. Conclusions and Relevance: The systematic use of OCT, FA and OCT‐A imaging can facilitate the diagnostic accuracy for detection and follow‐up of CNV activity in PXE. While structural OCT is of high value, especially when longitudinal follow‐up images are available, FA and OCT‐A data might contribute to diagnostic accuracy in more complex cases.